Bioinspired nanocellulose aerogel from spent coffee grounds and natural melanoidins for solar-driven desalination - Dan Wang; Xiaofan Chen; Xueyan Tang; Ruofei Zhu (Desalination, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Stepwise extraction of silicon and aluminum from nitric acid leach residue via sodium carbonate roasting and leaching - Fang Chen; Xue Ma; Lijun Jiang; Ruofei Du; Liangfeng Li; Laibao Liu; Xia Li; Bingyan Fan (Hydrometallurgy, 2026)

The deep colour consistency correction network for remote sensing images - Qingyang Li; Ruofei Zhong; Zhizhong Kang; Shihong Du; Wenqiang Lu; Xin Du; Yichun Chen (International Journal of Remote Sensing, 2026)

A multi-view depth-camera point cloud processing pipeline for pre-harvest maize stand counting - Ruofei Ma; Yuefeng Du; Lei Liu; Dafang Guo; Linze Wang; Du Chen; Zhenghe Song (Biosystems Engineering, 2026)

The research of a novelty bio-based flame retardant derived from the synthetic combination of alkaline-extracted polymer substances from wastewater sludge with phytic acid - Congcong Li; Ming Cheng; Ruiqin Chen; Ruofei Wang; Xiangyang Wang; Liang Zhao; Xiaodi Hao; Chen Shi; Wei Zhang (Journal of Environmental Management, 2026)

From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

Construction of an efficient synergistic catalytic system using DBD plasma and Fe-TiO2-rGO/HCP catalytic coating for ofloxacin removal - Ming Li; Liang Guo; Yimo Zhao; Shanshan Huang; Ruofei Jia; Lijiao Zheng; Yongyang Chen; Shanping Li (Journal of Contaminant Hydrology, 2026)

Clinical management of autoimmune liver diseases: juncture, opportunities, and challenges ahead - Yangfan Chen; Ruofei Chen; Haiyan Li; Zongwen Shuai (Immunologic Research, 2025)

Localized strain induced carrier separation and filtering in S-scheme MgIn2S4@CdS heterojunction for boosting selective CO2 photoreduction - Xing'’an Dong; Weidong Dai; Chen Yang; Xiaoqian Li; Ruofei Tang; Xian Shi (Chemical Engineering Journal, 2025)

A candidate multi-epitopes vaccine against encephalomyocarditis virus confers protection in mice - Hongshan Li; Rongrong Cheng; Pingan Dong; Yongfang Chen; Rongqian Mo; Jiayu Yue; Dianyu Li; Yanmei Yang; Amjad Ali; Xiangrong Li; Ruofei Feng (Veterinary Microbiology, 2025)

Impacts of major sports events on air pollution in host cities: A case study of the Nanjing Youth Olympic games - Ruofei Lin; Shanlang Lin; Ziyang Chen; Tian Yu (Urban Climate, 2025)

Microbial inoculants addition increases microbial necromass but decreases plant lignin contribution to soil organic carbon in rice paddies - Quanyi Hu; Xuelin Zhang; Ziwei Zhang; Ruofei Wang; Cheng Feng; Yingxin Xie; Shaojie Chen; Tianqi Liu (Soil and Tillage Research, 2025)

Revealing the excellent catalytic combustion ability of Cu1.5Mn1.5O4 (222) crystal facet with octahedrally coordinated Mn(Ⅳ)O6 site - Jian Deng; Chunhao Wang; Shenggui Ma; Chengchao Liu; Yongtao Zheng; Haipeng Chen; Ruofei Chen; Siyu Wei; Shanbi Peng; Xia Jiang (Journal of Environmental Chemical Engineering, 2025)

Extracellular vesicles engineered to directly target encephalomyocarditis virus ameliorates multi-organ viremia in a lethal infection model - Jiayu Yue; Yanmei Yang; Adi Idris; Wenjing Jin; Yaxin Zhang; Yongfang Chen; Xiangrong Li; Huixia Li; Shasha Li; Yanqiao Wen; Ruofei Feng; Jingying Xie (Veterinary Microbiology, 2025)

Impact performance of curved double arrow and stacked Miura-ori panels - Zhejian Li; Lingfeng Wang; Ruofei Yan; Yuanpeng He; Hong Hao; Yuanzheng Lin; Wensu Chen (Engineering Structures, 2025)

High dielectric sulfonyl-containing polyimide binders optimize the long-term stability and safety of NCM811 lithium-ion batteries at high voltages - Lin Chen; Dandan Yang; Junhao Xin; Xiaowei Zhou; Yuchen Zhang; Zixin Lv; Tiegen Guo; Qinghai Chen; Ruofei Gao; Ying Wang; Ning Wang; Shuanyan Kang; et al. (Chemical Engineering Journal, 2025)

OR-LIM: Observability-aware robust LiDAR-inertial-mapping under high dynamic sensor motion - Yangzi Cong; Chi Chen; Bisheng Yang; Ruofei Zhong; Shangzhe Sun; Yuhang Xu; Zhengfei Yan; Xianghong Zou; Zhigang Tu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Body fluid multiomics in 3PM-guided ischemic stroke management: health risk assessment, targeted protection against health-to-disease transition, and cost-effective personalized approach are envisaged - Ruofei Chen; Xiaoyan Wang; Na Li; Olga Golubnitschaja; Xianquan Zhan (EPMA Journal, 2024)
Because of its rapid progression and frequently poor prognosis, stroke is the third major cause of death in Europe and the first one in China. Many independent studies demonstrated sufficient space for prevention interventions in the primary care of ischemic stroke defined as the most cost-effective protection of vulnerable subpopulations against health-to-disease transition. Although several studies identified molecular patterns specific for IS in body fluids, none of these approaches has yet been incorporated into IS treatment guidelines. The advantages and disadvantages of individual body fluids are thoroughly analyzed throughout the paper. For example, multiomics based on a minimally invasive approach utilizing blood and its components is recommended for real-time monitoring, due to the particularly high level of dynamics of the blood as a body system. On the other hand, tear fluid as a more stable system is recommended for a non-invasive and patient-friendly holistic approach appropriate for health risk assessment and innovative screening programs in cost-effective IS management. This article details aspects essential to promote the practical implementation of highlighted achievements in 3PM-guided IS management.

Treating reverse osmosis brine of petrochemical wastewater using preparative vertical-flow electrophoresis (PVFE) with multi-objective optimization by response surface method - Rongbo Chen; Tian Tian; Ruofei Jin; Ze Liu; Wang Fu; Qiuyan Ji; Jiti Zhou (Environmental Science and Pollution Research, 2024)

Ubiquitinomics revealed disease- and stage-specific patterns relevant for the 3PM approach in human sigmoid colon cancers - Hua Yang; Na Li; Liang Chen; Lei Zhou; Yuanchen Zhou; Jixiang Liu; Wenshuang Jia; Ruofei Chen; Junwen Su; Lamei Yang; Xiaoxia Gong; Xianquan Zhan (EPMA Journal, 2023)

Dishevelled segment polarity protein 2 promotes gastric cancer progression through Wnt/β-catenin pathway - Ruofei He; Yu Chen; Chenyu Qian; YiLin Hu; Xinkun Huang; Ran Tao (Tissue and Cell, 2023)

AFLI-Calib: Robust LiDAR-IMU extrinsic self-calibration based on adaptive frame length LiDAR odometry - Weitong Wu; Jianping Li; Chi Chen; Bisheng Yang; Xianghong Zou; Yandi Yang; Yuhang Xu; Ruofei Zhong; Ruibo Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Spatial and Seasonal Variations in the Stable Isotope Values and Trophic Positions of Dominant Zooplankton Groups in Jiaozhou Bay, China - Zhixin Ke; Ruofei Li; Danting Chen; Chunyu Zhao; Yehui Tan (Frontiers in Marine Science, 2022)
The spatial and seasonal distributions of stable carbon and nitrogen isotopes (δ 13 C and δ 15 N) in dominant zooplankton groups were investigated in Jiaozhou Bay. Zooplankton δ 13 C values ranged from −22.89‰ to −15.86‰, and δ 15 N values ranged from 3.18‰ to 13.57‰, respectively. The δ 13 C and δ 15 N values generally followed the order of small zooplankton < large calanoids < small Sagitta < large Sagitta . Spatial distribution patterns of zooplankton δ 13 C and δ 15 N values varied in different seasons. Our results suggested that the spatial variation of δ 13 C was mainly controlled by terrigenous organic matter (OM) input and phytoplankton biomass, but water temperature may have played a key role in the seasonal variation of δ 13 C. In spring, the high phytoplankton biomass might increase the δ 13 C value of small zooplankton in the inner bay. During other seasons, the δ 13 C values of zooplankton generally increased from the inner bay to the outer bay, which might be associated with the influence of 13 C-depleted terrigenous OM carried by the river discharge. Small zooplankton stable isotope values were significantly correlated with that of particulate organic matter (POM). The influence of anthropogenic nutrient input on isotopic baseline can be cascaded to the zooplankton, and the effect might be weak at higher trophic levels. The Bayesian standard ellipse areas of dominant zooplankton groups were generally smallest in the winter, suggesting a narrow niche width during that time. The niche partition between small zooplankton, large calanoids, and Sagitta was most distinct in winter, and followed by summer. The relative trophic level of Sagitta ranged from 2.23 to 4.01, which generally declined from the inner bay to the outer bay during the spring, autumn, and winter seasons. High anthropogenic nutrient loading might reduce the difference in trophic niches among zooplankton groups. This study provided detailed information on the distribution of zooplankton δ 13 C and δ 15 N in a coastal bay, which will be useful for understanding the anthropogenic influence on the ecosystem structure and function.

Market integration and green economic growth—recent evidence of China’s city-level data from 2004–2018 - Jieping Chen; Xiaoli Hu; Junpei Huang; Ruofei Lin (Environmental Science and Pollution Research, 2022)

Acetone adsorption capacity of sulfur-doped microporous activated carbons prepared from polythiophene - Junchao Zhu; Ruofei Chen; Zheng Zeng; Changqing Su; Ke Zhou; Yamian Mo; Yang Guo; Fan Zhou; Jie Gao; Liqing Li (Environmental Science and Pollution Research, 2019)

Effects of sludge lysate for Cr(VI) bioreduction and analysis of bioaugmentation mechanism of sludge humic acid - Hongling Chen; Ruofei Jin; Guangfei Liu; Tian Tian; Chen Gu; Jiti Zhou; Defeng Xing (Environmental Science and Pollution Research, 2019)